Kepatuhan komunikasi SBAR dalam pelaksanaan transfer pasien ruang rawat inap ke ruang intensif oleh PPJA di ruang rinjani: Studi kasus - Wanda, Ira Purba; Asmaningrum, Nurfika; Faradisa, Elok; Suparman, Maman (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Communication failure during critical patient transfer is a leading cause of patient safety incidents globally. Despite available standards, implementation gaps frequently occur due to high workloads and dynamic clinical situations. Purpose: To analyze the compliance level of SBAR communication during patient transfer from inpatient wards to the intensive care unit. Method: This research is a case study with a descriptive observational design conducted in November 2025. The population included Primary Nurses (PPJA) in the Rinjani Ward. A sample of 14 respondents was selected via accidental sampling. Data were collected through direct observation using a checklist adopted from the hospital's Standard Operating Procedures (SPO). Results: The overall compliance level of SBAR communication was high, averaging 92%, supported by the dominance of nurses with over 5 years of experience and Ners education background. However, a critical gap was found in the read-back verification element (TBAK), which only reached 60%. Conclusion: While a safety culture is established, the closed-loop communication cycle remains incomplete, particularly in the verification aspect.   Keyword: Adherence; SBAR communication; Transfer Patient.   Pendahuluan: Kegagalan komunikasi selama transfer pasien kritis merupakan penyebab utama insiden keselamatan pasien secara global. Meskipun standar baku tersedia, kesenjangan implementasi komunikasi sering terjadi akibat beban kerja tinggi, dan situasi klinis yang dinamis. Tujuan: Untuk menganalisis tingkat kepatuhan komunikasi SBAR dalam pelaksanaan transfer pasien dari ruang rawat inap ke ruang intensif. Metode: Penelitian ini merupakan studi kasus dengan pendekatan deskriptif observasional. Populasi penelitian adalah Perawat Penanggung Jawab Asuhan (PPJA) di Ruang Rinjani dengan sampel sebanyak 14 responden yang diambil menggunakan teknik accidental sampling pada bulan November 2025. Pengumpulan data dilakukan melalui observasi langsung menggunakan lembar checklist sesuai SPO rumah sakit. Hasil: Kepatuhan komunikasi SBAR secara umum tergolong tinggi dengan rata-rata 92%, didukung oleh dominasi perawat dengan masa kerja <5 tahun dan latar belakang pendidikan Ners. Namun, ditemukan kesenjangan kritis pada elemen verifikasi ulang (read-back) yang hanya mencapai 60%. Simpulan: Meskipun budaya keselamatan telah terbentuk, siklus komunikasi tertutup (closed-loop) belum sempurna akibat faktor situasional.   Kata kunci: Kepatuhan; Komunikasi SBAR; Transfer Pasien.